2012
DOI: 10.1017/s204579601200042x
|View full text |Cite
|
Sign up to set email alerts
|

The role of cognitive functioning in the outcome of those at clinical high risk for developing psychosis

Abstract: Although it is well established that cognitive impairment is a common feature of schizophrenia, only recently has cognitive functioning been prospectively studied in individuals at clinical high risk (CHR) for developing psychosis. To date, both cross-sectional and longitudinal studies have been conducted in the CHR population and in the context of later conversion to psychosis. A comprehensive review of the literature suggests that CHR individuals have general and specific baseline cognitive deficits compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 48 publications
5
29
0
3
Order By: Relevance
“…A sixth possible limitation is that the use of a statistical correction such as the Bonferroni method was not applied for multiple comparisons. A seventh limitation is that despite there being inconclusive evidence for this in the literature (Addington and Barbato, 2012) it is possible that prodromal symptoms may have affected performance on IQ. Finally, only 72% of family member diagnoses of psychosis could be confirmed in the current study via SCID interview or formal records.…”
Section: Discussionmentioning
confidence: 99%
“…A sixth possible limitation is that the use of a statistical correction such as the Bonferroni method was not applied for multiple comparisons. A seventh limitation is that despite there being inconclusive evidence for this in the literature (Addington and Barbato, 2012) it is possible that prodromal symptoms may have affected performance on IQ. Finally, only 72% of family member diagnoses of psychosis could be confirmed in the current study via SCID interview or formal records.…”
Section: Discussionmentioning
confidence: 99%
“…It has been consistently reported that similar or less severe deficits in neurocognition, social cognition and functional outcome are observed in CHR individuals when compared to individuals at either their first episode or those who have a more chronic course of illness (Addington and Barbato, 2012; Thompson et al, 2011; Addington et al, 2008; Fusar-Poli et al, 2012b; Green et al, 2012). Although deficits in neurocognition (Fusar-Poli et al, 2012b) may play a role in predicting transition to psychosis in individuals at CHR, only one study to date has demonstrated that a combination of neurocognitive tasks and social cognition assessed by a theory of mind task was related to conversion (Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…In addition to attenuated psychotic symptoms, which all participants need to have to meet CHR criteria, both cognition and social functioning have continually been demonstrated to be among the most common deficits observed in those at CHR. [14][15][16][17] Enhancing the Prospective Prediction of Psychosis (PREDICT)is a 2-year longitudinal study to determine predictors of conversion in individuals at CHR of developing psychosis, conducted at the Universities of Toronto, North Carolina, and Yale. The main hypothesis of this study was that social functioning would be the best predictor of later transition to psychosis with cognition also being an important predictor.…”
Section: Introductionmentioning
confidence: 99%